Quantitative Analysis of TikTok Addiction: A User Behavior Study - Risalah, Aisyah Mujahidah; Rina, Nofha (Lingkar Studi Komunikasi (LISKI), 2025)
The use of the TikTok application has now reached all levels of society, especiallyteenagers who use the TikTok application as a medium to express themselves. This can certainly helpin some cases, but it can also create addiction to using the application. Researchers focused on theaddictive behavior displayed by TikTok users in the city of Jakarta. This research uses descriptivequantitative to understand and analyze the addictive behavior of TikTok users. The data obtained inthis research was obtained through observation, survey and interviews. This research aims tounderstand and analyze the addictive behavior of TikTok users. The addiction theory in this researchis based on Young's views using the Bergen Social Media Addiction Scale. There are six aspects ofaddiction, namely Salience, Tolerance, Mood swings, Withdrawal, Relapse and Conflict. The methodused is quantitative descriptive, to find out more about the addiction experienced by TikTok users.Based on the findings, 74.8% of TikTok users experience addiction, with the biggest aspect beingchanges in mood by using TikTok to seek entertainment